Saliva in identification of ABO Blood Grouping & Rhesus Factor (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: To assess the efficacy and reliability of saliva in identification of ABO blood grouping.Materials and Method: The study was conducted in the outpatient department of Oral Medicine andRadiology. The serum and saliva of 50 participants were collected and the blood group of the individual fromserum was identified by the slide agglutination method and from saliva by the absoption elution method.Results: Data obtained were subjected to statistical analysis using Paerson’s chi square test and it showedhigh significance (P = <0.001).Conclusion: The outcome of the present study showed that saliva can be used as an aid in forensics foridentification of ABO blood grouping of an individual.